2008
DOI: 10.1002/jbm.b.31162
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion of machined titanium dental implants under inflammatory conditions

Abstract: The effects of hyperglycemia, altered cell function, or inflammatory mediators on implant corrosion are not well studied; yet, these effects are critical to implant biocompatibility and osseointegration. Because implant placement is burgeoning, patients with medically compromising systemic conditions such as diabetes are increasingly receiving implants, and the role of other inflammatory diseases on implant corrosion also needs investigation. In the current study, the corrosion properties of commercially avail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
50
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 45 publications
(64 reference statements)
4
50
0
Order By: Relevance
“…The higher the concentration of the combined DEX-LPS, the lower the corrosion potential of the smooth Ti. The reduced values (more electronegative) of E corr suggest that the smooth Ti provides a less stable surface [21], [22] that may be a result of decreased surface passivity. A previous study related the passivity to the thickening of the oxide/hydroxide layer in the titanium/electrolyte interface [21].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The higher the concentration of the combined DEX-LPS, the lower the corrosion potential of the smooth Ti. The reduced values (more electronegative) of E corr suggest that the smooth Ti provides a less stable surface [21], [22] that may be a result of decreased surface passivity. A previous study related the passivity to the thickening of the oxide/hydroxide layer in the titanium/electrolyte interface [21].…”
Section: Discussionmentioning
confidence: 99%
“…Messer et al [22] evaluated the electrochemical behavior of commercially pure Ti implants (cpTi) in inflammatory and hyperglycemic conditions. The corrosion potential shifted to noble values at high concentrations of dextrose (15 mM) at the same concentration used in this study, as a function of monocyte cultures and blood cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because Ti is more readily oxidised than Ni, so the biologically inert Ti-oxide layer and extracellularderived calcium-phosphate layer on the Ni-Ti surface prevent the release of Ni (Es-Souni and Fischer-Brandies, 2005). However, since Ti-oxide is a very brittle ceramic, it can be damaged during dynamic mechanical loading (Peitsch et al, 2007) or under infl ammatory conditions (Messer et al, 2009), leading inevitably to the initiation of corrosion and increased release of Ni ions, causing local or systematic adverse health effects (Das et al, 2008). This could lead to necrotic and apoptotic changes of the tissue surrounding the implant (Bogdanski et al, 2004), increased expression of infl ammatory mediators such as tumour necrosis factor-alpha (TNF-α) and interleukin 6 (IL-6) and reduced proliferation of cells near the implant (Es-Souni and Fischer-Brandies, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Implants made of titanium materials also release metal ions into the body. Messer et al [23] exposed titanium implants to several solutions, and found that they had a risk of corrosion. Hence, coatings are necessary to protect the implants in a body environment.…”
Section: Discussionmentioning
confidence: 98%